Essays on sectoral adjustment in an open economy - Ylönen, Sakari (1989)
This study examines sectoral effects of different exogenous changes, and dynamics of sectoral adjustment. The study contains five theoretical essays in which we make various assumptions about production structure, wage determination and labor mobility. We present in a new way elasticities of factor demands and substitution under decreasing returns to scale. These results are used when we interpret sectoral effects of an increase in labor endowment. Furthermore, these results are exploited when we study effects of increased output or price of an intermediate good on traded and non-traded final good sectors under rigid nominal and real wages. A model of three stage production structure and short-run labor immobility is constructed, and spending, wealth and labor movement effects are distinguished. Dynamics of sectoral adjustment is studied when intersectoral mobility of labor force is not perfect and the booming sector is a wage leader which is followed by the contracting sector. Characteristics of adjustment paths are shown to unveil under certain conditions under- and overshooting of sectoral employments and outputs.